Cover Feature: RhII‐Catalyzed De‐symmetrization of Ethane‐1, 2‐dithiol and Propane‐1, 3‐dithiol Yields Metallo‐β‐lactamase Inhibitors (ChemMedChem 22/2021). (19th November 2021) - Krasavin, Mikhail; Zhukovsky, Daniil; Solovyev, Igor; Barkhatova, Darina; Dar'in, Dmitry; Frank, Denia; Martinelli, Giada; Weizel, Lilia; Proschak, Anna; Rotter, Marco; Kramer, Jan S.; Brunst, Steffen; et al.
Abstract : The Cover Feature shows the general mode of action of thiol‐based metallo‐beta‐lactamase inhibitors. The hero in the desert represents a person administering such an inhibitor. The whip in his hands (with the thiol group at the end) represents the monothiol metallo‐beta‐lactamase inhibitor which deprives the bacteria from using their metallo‐beta‐lactamase defense mechanism (represented by the scissors) to inactivate the antibiotic. More information can be found in the Full Paper by Mikhail Krasavin, Ewgenij Proschak et al.